Chained sweet: nanoconfinement of carbohydrates - Wiebenga-Sanford, Benjamin P., author; Levinger, Nancy, advisor; Fisher, Ellen, committee member; Barisas, George, committee member; Menoni, Carmen, committee member; Graham, James, committee member (Colorado State University. Libraries, 2017)
Sugars and other carbohydrates play critical roles in a vast array of chemical and biological systems. In biological systems, the carbohydrates' environments are highly heterogeneous, including interfaces in cells and subcellular organelles, and on proteins. Nanoconfined aqueous environments also feature in these naturally and artificially occurring systems. The studies reported here explore glucose and other carbohydrate molecules, specifically ethylene glycol, glycerol, meso-erythritol, xylitol, sorbitol, myo-inositol, and trehalose, in the nanoconfined environments offered by reverse micelles, also referred to as water-in-oil mocroemulsions. I investigate how the nanoconfinement affects the carbohydrate behavior and how the carbohydrates affect the reverse micelles. I report the effect of carbohydrates on report the loading-ability of carbohydrates into the reverse micelles, demonstrate the location of the carbohydrates in the reverse micelle water pools, and show an unexpected effect where the carbohydrates to add to the reverse micelle volume without appearing to take up space. I use EXSY or Z-Z exchange spectroscopy to show that that the exchange rate between water and carbohydrate hydroxyl groups is substantially slower than it is in bulk aqueous solution and that it does not depend on hydrogen bonding between the carbohydrate and surfactant headgroup. These reverse micellar environments can provide unique platforms for confinement and as model systems for biological constructs. Results from these studies provide fundamental information to help us understand, predict and control carbohydrates, in particular glucose, in biological systems. Finally, I report on experiments utilizing steady-state fluorescence spectroscopy to characterize the nature of the reverse micellar interior, specifically the local "viscosity" via the response of a dye probe molecule. I also detail experiments that aimed to measure the aggregation number, that is, the number of surfactant molecules in the reverse micelles of varying water and carbohydrate loading. Although interesting, these studies did not yield the desired results.
Keywords: glucose; NMR; reverse micelles; nanoscopic aqueous environments; carbohydrates; proton exchange